46.3k views
3 votes
م
Let f(x) =X²-4 and g(x) = 3x+2
3f(x)+2g(x)=

2 Answers

3 votes

Answer:


\boxed{\sf 3f(x) + 2g(x)= 3 {x}^(2) + 3 x - 8}

Given:

f(x) = x² - 4

g(x) = 3x + 2

To Find:


\sf 3f(x) + 2g(x)

Explanation:


\sf \implies 3f(x) + 2g(x) \\ \\ \sf \implies 3( {x}^(2) - 4) + 2(3x + 2) \\ \\ \sf \implies (3 * {x}^(2) ) - (3 * 4) + (2 * 3x) + (2 * 2) \\ \\ \sf \implies 3 {x}^(2) - 12 + 3x + 4 \\ \\ \sf \implies 3 {x}^(2) + 3x + ( - 12 + 4) \\ \\ \sf \implies 3 {x}^(2) + 3 x - 8

User David Dao
by
5.1k points
6 votes

====================================

م Let f(x) =X²-4 and g(x) = 3x+2 3f(x)+2g(x)=-example-1
م Let f(x) =X²-4 and g(x) = 3x+2 3f(x)+2g(x)=-example-2
User Sayan Pathak
by
5.5k points